Trans-Atlantic Transmission Of Interest Rate Shocks: Any Macroeconomic Concern For Nigeria? - Catherine Chidinma Mbah; Maria Chinecherem Uzonwanne; Kingsley Chidera Adonike; Innocent Acho Egbunike (International Journal of Economics Development Research (IJEDR), 2022)
The interconnectivity of global economies has created undue uncertainties in severeal domestic economies. As a result, this paper specifically investigates the trans-Atlantic transmission of interest rate shocks with a view to identifying any macroeconomic concern for Nigeria using Annual time series data from World Bank’s Development Indicators 2020. To achieve the objectives of this study, various econometric tests were carried out on the variables such as the Augmented Dickey- Fuller (ADF) test, variance decomposition test as well as the impulse response test. The impulse response analysis of our VAR model shows that Nigerian variables respond significantly to shocks from foreign variables. The study therefore concluded that shocks in Nigeria are mostly from across the Atlantic. In line with this, the study recommended that monetary authorities in Nigeria should base their policy making on foreign shocks with a view to stabilizing the macroeconomic environment.